ANALISIS EFISIENSI PEMASARAN TELUR AYAM RAS DI PETERNAKAN DESA KAMBINGAN, KACAMATAN TUMPANG, KABUPATEN MALANG - Yulius Ndara Walla; Cakti Indara Gunawan; Sumarno Sumarno (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine marketing channels, marketing margins, share of prices received by farmers and marketing efficiency. Determination of respondents for livestock business is done purposively. With the number of respondents as many as 30 people consisting of each breeder with the consideration that the selected respondents know the marketing flow of broiler eggs produced. While the determination of farmer respondents used is a descriptive method with a quantitative approach to determine the marketing margins, prices and marketing efficiency received by farmers so that 30 farmers each are obtained. in the goatan village farm, Tumpang sub-district, Malang district” as follows: 1). Breeders- Collectors. 2). Retailer - Consumer. The margin on the first channel is IDR 3,797-. and the second channel is Rp. 1,664-. The average price value received by all farmers is 83.6%. While the first efficiency value is 24.8%. And the second efficiency value is 6.9%. The results of this study also show that the efficiency value of the first marketing channel is greater than that of the second efficient channel